Pengembangan Bahan Ajar IPAS Berbantuan Wordwall Game Menggunakan Model PjBL untuk Meningkatkan Kemampuan Literasi dan Numerasi pada Siswa Sekolah Dasar - Pratiwi, Suharti Endang; Jufri, A Wahab; Gunawan, Gunawan (Indonesian Journal of Elementary and Childhood Education, 2024)
Low literacy and numeracy skills among elementary school students are a major concern in education. This research addresses this issue by developing innovative IPAS (Science, Social Studies, and Technology) learning materials that integrate the interactive game application Wordwall with a Project Based Learning (PjBL) approach. The aim is to create learning materials that are valid, practical, and effective in enhancing elementary students' literacy and numeracy skills. This Research and Development (R&D) study, following the Dick and Carey model, involved 25 fifth-grade students from SD Negeri 44 Cakranegara as the sample. Data collection was conducted through questionnaires for validity and practicality, and multiple-choice tests for the effectiveness of the learning materials. Data analysis utilized the N-Gain test and paired t-test. The results revealed a significant increase in students' literacy (14.84 points) and numeracy (19.80 points) skills after using the developed materials. This improvement was supported by the significant values obtained from the t-test (p < 0.05). This research confirms that innovation in learning materials and teaching methods, such as the use of Wordwall games and PjBL, can have a substantial positive impact on elementary school students' literacy and numeracy abilities.